Generation Z’s Intention to Apply: An Approach to Job Preferences, Organization Attractiveness, Person-Organization Fit, and Social Media Usage - Inta Hartaningtyas Rani; Jara Hardiyanti Jalih; Lestari Adhi Widyowati (Universitas Negeri Malang, 2022)
Talent wars reveal that a company’s different human capital can provide competitiveness and agility. Organizations should offer an attractive workplace location, considering the target’s expectations. Generation Z accounts for 19.42 percent of the global population and will make up most of the incoming workforce. Using the structural equation modeling (SEM), the study examines data on the intention to apply among 350 nearly-graduated college students. Findings support a significant positive impact of Generation Z job preferences and organizational attractiveness on their intention to apply for jobs. When choosing a career, the top three priorities for respondents are health insurance, a coaching manager, and job security. Recruitment messages in job ads should most likely appear on the company’s social media account, focusing on more psychological and organizational attributes that fit the preferences of generation Z, particularly job benefits. Instead of a mediating effect, person-organization fit and social media direct correlation robustly predict the intention to apply for a job. Keywords: Generation Z, Attractiveness, P-O fit, Social media, Intention to apply